International Partnerships in University-Level Music Education: Principles, Pivots, and Possibilities - Patrick K. Freer (MDPI AG, 2024)
This article reports an analytical review of research and policy concerning the qualities that create, sustain, and enliven academic partnerships between universities in different countries. This review provides context for a discussion of the development of the institutional partnership between the Universität Mozarteum Salzburg (Austria) and Georgia State University (United States of America). A scoping review of the literature suggests that such partnerships are viewed differently by those responsible for the legal agreement establishing the partnership, the faculty and students who are tasked with implementing the partnership, and outsiders who view the results of the partnership via publications, presentations, and performances. This review situates the analysis of the partnership with the identification of themes consistent with the broader literature, including a reflection on cultural awareness, access and equity, institutional and human capacity building, and ethical dilemmas. Implications include a reflection on the collaboration's COVID-19 era development, with the suggestion that the shift to virtual communication enhanced the partnership even as it disrupted the planned implementation.